El bienestar docente como piedra angular del éxito estudiantil en la Educación de Idiomas Extranjeros (en inglés) - Delgado-Fernández, Leandro; Sardiñas-Companioni , José Luis; Puerto-Valdés, Adis Eliany (Educación y sociedad, 2025)
This article delves deep into the crucial link between teacher wellbeing and student success. Through a qualitative exploratory and descriptive paradigm, the research includes a theoretical review, a survey, and a focus group to explore the current state of the multifaceted relationship between teacher wellbeing and the quality of learning and student outcomes in the Foreign Language Major at the University of Ciego de Ávila. The findings reveal that teacher wellbeing is decisive in ensuring student success, as happy and fulfilled teachers are more likely to provide positive, engaging, and effective learning experiences to their students. However, it is often hindered by numerous challenges, including burnout, excessive workload, lack of support, and inadequate compensation. These challenges can negatively impact teacher morale, job satisfaction, and performance, leading to decreased student engagement, achievement, and overall success. In response, a range of innovative and practical solutions to support teacher wellbeing are proposed, leading to happier teachers and more successful students.